Experimental evaluation of the effect of wave focusing walls on the performance of the Sea-wave Slot-cone Generator
The Sea-wave Slot-cone Generator (SSG) is a multi-level overtopping based wave energy converter thatcan be installed either nearshore or offshore. The installation in harbor breakwaters and in the shorelinepresents several advantages despite the usual exposure to smaller waves than at offshore locations. Thiswork analyzes the effect of wave focusing walls (i.e., wave concentrators) on the performance of isolatedSSG units using a physical model built on a geometric scale of 1/40. Seven configurations were defined bychanging the opening angle and the crest level of those elements. The use of wave concentrators provedto be advantageous since a wider wave front is captured and the run-up and overtopping phenomena areenhanced on the SSG ramp owing to the wave energy concentration (walls tapering effect). In fact, thetotal mean power captured increased for all SSG configurations with concentrators in comparison tothe base configuration (without concentrators), regardless of the sea state considered. In terms of hydraulic performance, the gain associated to the use of wave concentrators depends on the characteristics ofincident waves, being higher for the smaller significant wave heights and the shorter peak wave periods.The hydraulic efficiency, defined as the ratio between the total mean power captured per meter of SSGwidth and the wave power per meter width of the incident waves, increases with the significant waveheight and reduces with the peak wave period in all tested SSG configurations. In addition, in comparisonto the base configuration, the hydraulic efficiencies with concentrators were higher for the smaller significant wave heights, but smaller for the other sea conditions. The use of wave concentrators increasedthe annual energy production approximately to the double. Overall, the application of the SSG technologyin breakwaters presents itself as promising considering the characteristics of the wave resourcenearshore or even in onshore locations.